PTU-105 Outcome of Cirrhotic Patients Admitted to Intensive Care Units at Hospitals without Specialist Liver Services. (4th June 2013) - Beejooa, G; Oates, R; Loo, L; Mirza, N; Shah, S; Grimley, C; Watts, G; Prasad, N; Kochar, N; Rifai, A Al
Abstract : Introduction: Patients with liver cirrhosis admitted to an ICU are believed to have a poor prognosis with high mortality despite significant use of resources. Most of the literature to date on this topic has been collected at hospitals with Specialist Liver Units and these results may not be representative of the outcome at general ICUs. A recent prospective study of cirrhotic patients admitted to a tertiary Liver ICU in the UK demonstrated an overall hospital mortality of 59%. The aim of this study was to determine the outcome of cirrhotic patients admitted to non-specialist ICUs. Methods: Data was retrospectively collected from four hospitals in the NW region of the UK without specialist liver ICUs. Patients were identified using the Intensive Care National Audit and Research Unit (ICNARC) database. 61 patients with liver cirrhosis admitted to a general ICU between January 2010 and January 2012 were included in this study. Results: Age range was 30 to 79 years (average 51 years). 80% of patients were male and alcohol was the commonest aetiology for liver cirrhosis (90%). The main reason for admission to ICU was for gastrointestinal bleeding (38%). 51% of patients had a Child Pugh score of C on admission to ICU. 46% of patients had a MELD score between 10 and 19 and 28% had a score between 20 and 29. 79% of patients required invasive ventilatory support, 49% required vasopressors and 21% needed renal replacement therapy. 51% developed further decompensation of their liver disease during their ICU stay. These included GI bleeding (21%), hepatic encephalopathy (15%), HRS (11%) and SBP (3%). 67% of patients had an ICU stay of < 5 days. A 49% inpatient mortality rate was observed in our study with sepsis and multi-organ failure being the most common causes of death. Conclusion: Patients with liver cirrhosis admitted to general ICUs have similar rates of mortality compared to those in tertiary liver ICUs. Therefore, admission to such units should not be deemed futile in cirrhotic patients and earlier admission may improve outcome. Disclosure of Interest: None Declared